Is there a Kantian faculty for politics? Judgment and Publicity in Political and Moral Philosophy in 20th Century - De Vita, Valentina Dafne (Studia Kantiana, 2023)
The aims of this paper are two: on one hand I try to define the possibility of indicating in Kant´s works a political faculty; on the other hand, I try to define the relationship between politics and morals in his political theory. The first question of this paper seems to be a neglected aspect by Kantian researchers, who simply limit themselves to identify the political faculty either with practical reason (Hoffe) or with judgment (Düsing, Pries). For this reason I will compare some interpretations about the faculty of politics of authors from the 20th century such as Adorno, Arendt, Lyotard and Habermas, who discussed, from different prospectives, the reasons why the faculty of politics should be individualized in practical reason (Adorno and Habermas) -first section- or in judgment (Arendt and Lyotard) -second section. After a comparison of sensus communis with the principle of Publizität at the end of second section, I try to discuss why we need both Kantian faculties for politics. The answer to this question seems to be linked to the problematic of disagreement between the principle of politics with the that of morals, because the causes of the disagreement are not objective but subjective, meaning, they depend of the special status of mankind as sensitive and rational being.